2015
DOI: 10.1021/acsnano.5b04042
|View full text |Cite
|
Sign up to set email alerts
|

Photothermally Activated Pyroelectric Polymer Films for Harvesting of Solar Heat with a Hybrid Energy Cell Structure

Abstract: Photothermal effects in poly(3,4-ethylenedioxythiophene)s (PEDOTs) were explored for pyroelectric conversion. A poled ferroelectric film was coated on both sides with PEDOT via solution casting polymerization of EDOT, to give highly conductive and effective photothermal thin films of PEDOT. The PEDOT films not only provided heat source upon light exposure but worked as electrodes for the output energy from the pyroelectric layer in an energy harvester hybridized with a thermoelectric layer. Compared to a bare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(82 citation statements)
references
References 45 publications
0
82
0
Order By: Relevance
“…Seemingly, the intermittency issue can be circumvented, by alternatively intercepting and capturing of solar thermal energy fluxes. [25][26][27][28][29][30][31] Thermoelectric generator harvests energy via the Seebeck effect triggered by static temperature differences, while the pyroelectric generator delivers through the change of spontaneous polarization in response to dynamic temperature fluctuations. [18][19][20][21][22][23][24] Also, harvesting of ubiquitous low grade waste heat is presently perceived as a promising energy source toward decarbonized and sustainable ecology.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Seemingly, the intermittency issue can be circumvented, by alternatively intercepting and capturing of solar thermal energy fluxes. [25][26][27][28][29][30][31] Thermoelectric generator harvests energy via the Seebeck effect triggered by static temperature differences, while the pyroelectric generator delivers through the change of spontaneous polarization in response to dynamic temperature fluctuations. [18][19][20][21][22][23][24] Also, harvesting of ubiquitous low grade waste heat is presently perceived as a promising energy source toward decarbonized and sustainable ecology.…”
mentioning
confidence: 99%
“…[25][26][27][28][29][30][31] Thermoelectric generator harvests energy via the Seebeck effect triggered by static temperature differences, while the pyroelectric generator delivers through the change of spontaneous polarization in response to dynamic temperature fluctuations. [25][26][27][28][29][30][31] Thermoelectric generator harvests energy via the Seebeck effect triggered by static temperature differences, while the pyroelectric generator delivers through the change of spontaneous polarization in response to dynamic temperature fluctuations.…”
mentioning
confidence: 99%
“…Using the hybrid energy harvester, the Li-ion battery could be easily charged from 1 V to 3.7 V in only about 376 s. Under a constant discharging current of 5 mA, the charged Li-ion battery can continue to operate for about 327 s before it gets back to the original value of 1 V, corresponding to total electric capacity of 0.45 mA h. In 2015, Park et al reported a hybrid cell based on a DSSC solar cell with a pyroelectric and thermoelectric device operated by photothermally generated heat, as shown in . 87 The photoconversion efficiency (PCE) was increased up to 20% under sunlight irradiation (AM 1.5G) using the transmitted light through the DSSC as a heat source that was converted into electricity by the pyroelectric and thermoelectric effects simultaneously by the photothermal poly(3,4-ethylenedioxythiophene) (PEDOT) electrodes. Interestingly, as PV works under sunlight, the output voltage from the PV device continuously decreased because of the fast recombination phenomenon during the PV operation (Fig.…”
mentioning
confidence: 99%
“…The photothermal properties of CPs have been intensely investigated only in the fields of photothermal energy harvesting and cell engineering. [21][22][23][24][25][26] Therefore, the application of highly photothermal CPs, such as PEDOTs, into foldable bimorphs is an interesting challenge. The other challenge is the fabrication of bimorphs with CPs, which involves the transfer of a CP layer onto a soft layer.…”
Section: Introductionmentioning
confidence: 99%